Pengaruh Bauran Pemasaran Jasa Terhadap Kepuasan Anggota Pada Koperasi Syariah (Studi Kasus Pada Bmt Al-Ittihad Pekanbaru) - N, arizal; nofrizal, nofrizal (Jurnal Daya Saing, 2016)
The development in the business very rapidly also makes business more challenges in the financial services sector such as Bmt becomes increasingly large, increasingly fierce competition, and the use of increasingly sophisticated technology and consumers are increasingly varied. This condition is indirectly demanded Bmt to be able to further develop better strategies in marketing, production, employee, as well as in the financial sector so as to meets what the wants and needs of each of its customers as well as increase the number of members or customers. Like at Bmt Al Ittihad, which is one of the many cooperatives that have sharia potential to grow in pekanbaru, because Bmt Al Ittihad increased member / new customer every year. This research directed to address problems if the marketing mix consisting of product, prices, promotion, people, process, location and physical evidence and service quality then influence the satisfaction of members of Bmt Al Ittihad and the benefits of this research is expected to provide evaluation of policies and marketing strategies must be taken related to what the needs and tastes of members of Bmt Al Ittihad. These results indicate all variable have to influence simultaneous marketing mix consisting of product, promotion, process, price, employees, places, physical evidence and service quality. And then as test parsial results only physical evidence and place have to influence of satisfaction member of Bmt Al Ittihad. Keywords: Members Satisfaction, Marketing Mix Service and Service quality